2013
DOI: 10.1136/jnnp-2012-303356
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in cerebral venous thrombosis: a single centre experience

Abstract: This is the largest series on decompressive craniectomy for CVT in literature to date. Decompressive craniotomy should be considered as a treatment option in large venous infarcts. Very good outcomes can be expected especially if done early and in those below 40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 27 publications
2
65
1
2
Order By: Relevance
“…There appears to be no role for deciding the length of anticoagulation based on recanalisation because this only occurs during the first few months after CVT, and no correlation has been found between recanalisation and clinical outcome. 30 Finally, it is worth mentioning direct oral anticoagulants (DOACs). Studies have shown that DOACs are no less effective than warfarin in both the treatment of VTE and prevention of recurrence.…”
Section: Management Of Cvtmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be no role for deciding the length of anticoagulation based on recanalisation because this only occurs during the first few months after CVT, and no correlation has been found between recanalisation and clinical outcome. 30 Finally, it is worth mentioning direct oral anticoagulants (DOACs). Studies have shown that DOACs are no less effective than warfarin in both the treatment of VTE and prevention of recurrence.…”
Section: Management Of Cvtmentioning
confidence: 99%
“…4 Patients with rapid neurological deterioration because of impending herniation can benefit from decompression with craniectomy. 30,31 Following the immediate management of CVT, long-term vitamin K antagonists, such as warfarin, with a target international normalised ratio (INR) of 2-3 should be used. The duration of anticoagulation depends on aetiology.…”
Section: Management Of Cvtmentioning
confidence: 99%
“…The studies [123][124][125][126][127][128][129][130][131] included case reports (39 patients), case series (166 patients), two systematic reviews 125,131 and two non-randomised controlled studies. 123,124 The average death rate among patients treated with decompressive surgery (hemicraniectomy or haematoma evacuation) was 18.5%, the death or disability rate was 32.2%, the severe dependency rate only 3.4% and the complete recovery rate 30.7%.…”
Section: (Recommendations)mentioning
confidence: 99%
“…Surgical intervention can result in a good functional outcome even in the most severe cases of CVT 69 70. Early surgery (within 12 hours of admission), and younger patients are predictors of good outcome after decompressive craniectomy 68. There are no data to guide when to choose hemicraniectomy over endovascular management, or when and how to combine them in treating patients with severe thrombosis.…”
Section: Diagnosis and Managementmentioning
confidence: 99%